Case Report: An Infant With Kabuki Syndrome, Alobar Holoprosencephaly and Truncus Arteriosus: A Case for Whole Exome Sequencing in Neonates With Congenital Anomalies - Sakaria, Rishika P.; Zaveri, Parul G.; Holtrop, Shannon; Zhang, Jie; Brown, Chester W.; Pivnick, Eniko K. (Frontiers in Genetics, 2021)
Kabuki syndrome is a rare multiple anomalies syndrome associated with mutations in KMT2D or KDM6A. It is characterized by infantile hypotonia, developmental delay and/or intellectual disability, long palpebral fissures with everted lateral third of the lower eyelids and typical facial features. Intracranial anomalies occur infrequently in patients with KS and holoprosencephaly has only been recently described. Additionally, though congenital heart diseases are common in patients with KS, to our knowledge truncus arteriosus has never been reported in a patient with KS. We present an unusual case of KS in an infant with holoprosencephaly and truncus arteriosus with partial anomalous pulmonary venous return. Duo whole exome sequencing in our patient identified a pathogenic nonsense variant in exon 10 of KMT2D (c.2782C > T; p. Gln928*) establishing the diagnosis. This report further expands the phenotypic spectrum of patients with Kabuki syndrome and emphasizes the utility of performing large scale sequencing in neonates with multiple congenital anomalies.